Children's physical activity levels during primary school break times: A quantitative and qualitative research design. (February 2016) - Powell, Emma; Woodfield, Lorayne A; Nevill, Alan AM
The overall aim of this study was to assess the diversity of primary school children's physical activity (PA) during outdoor recess. The study was grounded in a mixed method approach, assisting in the identification of multifaceted predictors of children's PA, including insights to social behaviours during break time. Data were obtained from children aged 7–10 years across five primary schools in the West Midlands, United Kingdom. Data were collected during the English winter months from November 2013 to January 2014 and involved two distinct phases. In the quantitative phase ( n = 82), children's PA levels and social play behaviours were directly observed at break time using the system for observing children's activity and relationships during play (SOCARP).The SOCARP instrument coded 820 minutes of school break time across the categories of: physical activity; group size; activity type and social play behaviours. In the qualitative phase ( n = 80), children participated in group interviews in relation to their perceptions and experiences of the playground environment. Findings indicated boys and girls have different predictors of their PA levels. Participating in sports activities and engaging in large groups were positive predictors of boys' moderate to vigorous physical activity (MVPA), whereas pro-social interactions and small/medium groups were positive predictors of girls' MVPA. The qualitative findings highlighted several themes including: boys and sport; power hierarchies; girls' walk and talk; and imaginary play. Drawing from the current findings, it is suggested that interventions should focus on the social environment of break times, facilitating walk and talk routes for girls and sporting opportunities for boys.